2016
DOI: 10.1039/c6dt00218h
|View full text |Cite
|
Sign up to set email alerts
|

An Ag(i) energetic metal–organic framework assembled with the energetic combination of furazan and tetrazole: synthesis, structure and energetic performance

Abstract: A novel Ag(I) energetic MOF [Ag16(BTFOF)9]n·[2(NH4)]n () assembled with Ag(iI ions and a furazan derivative, 4,4'-oxybis[3,3'-(1H-5-tetrazol)]furazan (H2BTFOF) was successfully synthesized and structurally characterized, featuring a three-dimensional porous structure incorporating ammonium cations. The thermal stability and energetic properties were determined, revealing that the 3D energetic MOF had an outstanding insensitivity (IS > 40 J), an ultrahigh detonation pressure (P) of 65.29 GPa and a detonation ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…It crystallizes in the monoclinic space group P 2 1 /c with a calculated density of 3.2 g/cm 3 at 123 K (Supplementary Tables 2–6). The density value is the highest crystal density reported so far for any cyclo -N 5 ˉ complex 15 , and is largely due to the presence of four heavy silver atoms. As depicted in the Oak Ridge Thermal Ellipsoid plot (ORTEP) of [Ag(NH 3 ) 2 ] + [Ag 3 (N 5 ) 4 ]ˉ (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…It crystallizes in the monoclinic space group P 2 1 /c with a calculated density of 3.2 g/cm 3 at 123 K (Supplementary Tables 2–6). The density value is the highest crystal density reported so far for any cyclo -N 5 ˉ complex 15 , and is largely due to the presence of four heavy silver atoms. As depicted in the Oak Ridge Thermal Ellipsoid plot (ORTEP) of [Ag(NH 3 ) 2 ] + [Ag 3 (N 5 ) 4 ]ˉ (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Meanwhile, the self‐accelerating decomposition temperature ( T SADT ) and critical temperature of thermal explosion ( T b ), which are two important parameters to ensure safe storage and process operations, are also calculated (Table S2 in the Supporting Information). The six compounds show preferable thermal stability in the exothermic decomposition stage, in which the T SADT and T b of 6 are, respectively, 379.0 and 384.6 °C, exceeding common explosives like FOX‐7 (206.0 and 207.1 °C) and one of the most powerful IH‐ECPs, [Ag 16 (BTFOF) 9 ] n ⋅ [2(NH 4 )] n (228.2 and 241.2 °C) …”
Section: Resultsmentioning
confidence: 99%
“…[37,38] However,i deal insensitive high-energetic coordination polymers (IH-ECPs) conforming to the concept of IHEs with outstanding insensitivity (IS > 40 J, FS > 360 N) and detonation velocity( D > 9kms À1 )a re rare in the published literature. [39][40][41][42][43][44][45][46][47] To date, only two high-performance IH-ECPsh ave been constructed based on tetrazole derivatives:4 ,4'oxybis(3,3'-(1 H-5-tetrazol))furazan [46] and bis(tetrazole)methane. [47] As the primary energy source, these nitrogen-rich compounds not only have abundant inherent energetic bonds between atoms of C/N and N/N, but also will bring diversec oordination structures through high nitrogen aromatic moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have recently demonstrated the possibility of using nitrogen-rich MOFs as high explosives [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. MOFs consist of metal ions (Pb 2+ , Ag + , etc.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivities of these 3D MOFs are significantly lower than those of reported energetic coordination polymers, such as 1D (CHP, IS = 0.5 J) and 2D (ZnHHP, IS = 2.5 J; CHHP, IS = 0.8 J) MOFs. An increasing number of investigations on E-MOFs as new-generation high explosives were reported by Chen et al [32,33,36,38,39,40,42,44,45,50,51], Pang et al [28,48,52], Shreeve et al [49,53], and so on [41,47,54,55,56] because of the advantages of 3D MOFs.…”
Section: Introductionmentioning
confidence: 99%